Standard radiotherapy for patients with nasopharyngeal carcinoma results in progressive tract-specific brain white matter alterations: A one-year follow-up via diffusion tensor imaging. (June 2021) - Qiu, Yingwei; Guo, Zheng; Lin, Xiaoshan; Li, Jing; Li, Zhipeng; Han, Lujun; Yang, Yadi; Lv, Xiaofei
Highlights: Bilateral CAB fibers displayed progressive diffusion reduction over time with no detectable FA changes in NPC patients during the first year after RT. RT-associated progressive diffusion reduction in the left CAB correlated with longitudinal atrophy of the ipsilateral hippocampus. RT-associated progressive diffusion reduction in the left CAB correlated with progressive cognitive impairment in NPC patients following RT. Abstract: Background and purpose: Radiation therapy (RT)-induced neurocognitive disability may be mediated by brain tissue damage. The aim of the present study was to investigate the effects of standard RT on normal brain tissue via in vivo neuroimaging in patients with nasopharyngeal carcinoma (NPC). Materials and methods: A total of 146 newly diagnosed NPC patients who were treated with standard RT were longitudinally followed up at multiple time points during the first year post-RT, with 19 comparable healthy controls followed up in parallel serving as normal age-related benchmarks. Magnetic resonance diffusion tensor imaging was used to evaluate longitudinal brain white matter tract changes in NPC patients. The relationships between RT-related white matter changes, hippocampal atrophy, and cognitive impairment were also assessed. Results: Bilateral cingulate angular bundle (CAB) fibers had progressive diffusion reduction [radial diffusivity (RD) and mean diffusivity] over time ( P  < 0.05, corrected for multiple comparisons) in NPC patients during the first year after RT. RT-associated progressive RD reduction in the left CAB correlated with longitudinal atrophy of the ipsilateral hippocampus ( P  = 0.033). Additionally, RT-associated progressive RD reduction in the left CAB correlated with progressive cognitive impairment in NPC patients post-RT ( P  = 0.048). Conclusion: We present evidence of progressive RT-associated changes in the bilateral CAB in NPC patients, which may underlie RT-related cognitive impairment. These findings illustrate that the use of white matter tract alterations as potential biomarkers to detect RT-related brain injury in NPC patients may be useful for better understanding the pathogenesis of RT-induced cognitive decline.